SENESCENCE: DEFINITION, MECHANISMS OF OCCURENCE AND DETECTION IN TISSUES - Mijajlovic, Vladimir (Medicinski podmladak, 2023)
ABSTRACT: Cellular senescence represents a state, which is defined as a stable blockage of cellular cycle in the G1 phase, as an answer to multiple triggers and their qualitative and quantitative characteristics. Next to the blockage of the cellular cycle, the cellular senescence process is very dynamic. The process includes different morphological and intracellular changes, gene expression changes, epigenetic modification, macromolecular damages, cellular metabolism deregulation and appearance of complex proinflammation secretory phenotype, which is powerful modulator and contributor in many biochemical processes, not only in senescent cells, but also in their neighboring areas. Cellular senescence may have, next to the already mentioned autocrine, also a paracrine effect on the close and more distant surrounding. In past decades, in both in vivo and in vitro experiments, physiological and pathological influences of cellular senescence, on numerous processes in the human body, have been proven and documented. In particular, oncogene induced cellular senescence (under in vitro conditions), has shown significant influence of this process on the suppression of tumorigenesis. Cellular senescence does not only suppress proliferation and promotion of tumour cells, but it also facilitates their removal through the process of immunological surveillance. In case immunological surveillance is not successful, senescent cells may lead to the state of chronical inflammation of the microenvironment (through different biochemical processes), which leads to the initiation of the tumour formation, and later migration, angiogenesis, and final metastasis and implementation of tumour cells in remote parts of the human body. Next to all mentioned, cellular senescence may be initiated as an answer to a genotoxic stress, caused by the received therapy. Therefore, detection of senescence cells after the therapy, together with their monitoring is a key step to early detection of premalignant events, as well as to the application of adequate preventive and early therapeutic protocols.